Toxic Peptide From Palythoa caribaeorum Acting on the TRPV1 Channel Prevents Pentylenetetrazol-Induced Epilepsy in Zebrafish Larvae - Wang, Xiufen; Liao, Qiwen; Chen, Hanbin; Gong, Guiyi; Siu, Shirley Weng In; Chen, Qian; Kam, Hiotong; Ung, Carolina Oi Lam; Cheung, Kwok-Kuen; Rádis-Baptista, Gandhi; Wong, Clarence Tsun Ting; Lee, Simon Ming-Yuen (Frontiers in Pharmacology, 2021)
PcActx peptide, identified from the transcriptome of zoantharian Palythoa caribaeorum, was clustered into the phylogeny of analgesic polypeptides from sea anemone Heteractis crispa (known as APHC peptides). APHC peptides were considered as inhibitors of transient receptor potential cation channel subfamily V member 1 (TRPV1). TRPV1 is a calcium-permeable channel expressed in epileptic brain areas, serving as a potential target for preventing epileptic seizures. Through in silico and in vitro analysis, PcActx peptide was shown to be a potential TRPV1 channel blocker. In vivo studies showed that the linear and oxidized PcActx peptides caused concentration-dependent increases in mortality of zebrafish larvae. However, monotreatment with PcActx peptides below the maximum tolerated doses (MTD) did not affect locomotor behavior. Moreover, PcActx peptides (both linear and oxidized forms) could effectively reverse pentylenetetrazol (PTZ)-induced seizure-related behavior in zebrafish larvae and prevent overexpression of c-fos and npas4a at the mRNA level. The excessive production of ROS induced by PTZ was markedly attenuated by both linear and oxidized PcActx peptides. It was also verified that the oxidized PcActx peptide was more effective than the linear one. In particular, oxidized PcActx peptide notably modulated the mRNA expression of genes involved in calcium signaling and γ-aminobutyric acid (GABA)ergic-glutamatergic signaling, including calb1, calb2, gabra1, grm1, gria1b, grin2b, gat1, slc1a2b, gad1b and glsa. Taken together, PcActx peptide, as a novel neuroactive peptide, exhibits prominent anti-epileptic activity, probably through modulating calcium signaling and GABAergic-glutamatergic signaling, and is a promising candidate for epilepsy management.